Vivienda Labor de colectivos: hacia la democratización del hábitat social en Cumaribo Vichada (2022)
OThe conformation of housing and its daily influence is one of the issues that society raises the most in relation to their daily work. This graduate work addresses the issue of adequate housing as a possible solution to the population and housing deficit in the municipality of Cumaribo, in the Colombian department of Vichada; the 7 elements of housing proposed by the UN are taken as a starting point, where quality is identified from two perspectives, one quantitative and the other qualitative, the first refers to the physical characteristics of housing, as well as its environment; the second has to do with the relationship between man and territory, that is, the interactions that human beings have with the popular habitat.